Lumbar disc syndrome in Finland. Issue 3 (September 1987) - Heliövaara, M; Impivaara, O; Sievers, K; Melkas, T; Knekt, P; Korpi, J; Aromaa, A
Abstract : The prevalence of lumbar disc syndrome (herniated disc or typical sciatica) and its consequences in terms of disability, handicap, and need for medical care were studied as part of the Mini-Finland Health Survey. A sample of 8000 persons representative of the Finnish population aged 30 or over was asked to come for examination, and 7217 (90%) participated. A diagnosis of lumbar disc syndrome based on medical history, symptoms, and standardised physical examination was made for 5.1% of the men and for 3.7% of the women. Half of these patients were assessed to be in need of medical care, over 80% of which was considered to be adequately met. One third of all patients with lumbar disc syndrome had been previously hospitalised for that syndrome, and one fifth of the patients had undergone lumbar surgery. At least slight disability was found in almost 60% of the patients, though severe functional limitations were rare. About 6% of the population's work disability was estimated to be attributable to lumbar disc syndrome.